Growth, Body Composition, and Lung Function in Prepubertal Children with Cystic Fibrosis Diagnosed by Newborn Screening. (10th December 2020) - Owen, Elizabeth; Williams, Jane E; Davies, Gwyneth; Wallis, Colin; Grant, Robert L; Fewtrell, Mary S
Abstract: Background: Children with cystic fibrosis (CF) are at risk of altered body composition (BC). Newborn screening (NBS) may lead to improved BC outcomes. We investigated BC and its relationship with lung function in prepubertal children diagnosed with CF by NBS. Secondary aims explored predictors of fat‐free mass (FFM) and lung function. Methods: Thirty‐seven screened (non‐meconium ileus) children with CF (20 boys) born 2007–2012 had a dual‐energy x‐ray absorptiometry scan at 5–8 years to determine whole‐body (WB) and appendicular BC. Anthropometry was performed and routine spirometry recorded. Results were converted to z ‐scores, height‐adjusted (fat mass index [FMI] and FFM index [FFMI]) and compared with population mean values. Predictors of forced expiratory volume in 1 second (FEV1 ) were assessed using linear regression. Results: Height, body mass index (BMI), and FEV1 were within normal limits, however, weight and BC were significantly low compared with reference data (weight, P = .03; WB FMI, P = .001; WB FFMI, P = .009). Gender differences were detected, with lower appendicular BC in boys and lower weight, BMI, and BC in girls. The association between FEV1 and WB FFMI ( r = 0.38; P = .02) was stronger than with BMI ( r = 0.29; P = .08). WB FFMI was the only significant predictor of FEV1 in a multivariable model (95% CI, 0.11–0.99; P = .016). Conclusion: In this NBS CF population, gender differences in growth and BC were apparent despite preserved lung function. These results support BC assessment in prepubertal children, particularly girls, with an opportunity to direct interventions to optimize FFM.